2020
DOI: 10.1039/c9an02226k
|View full text |Cite
|
Sign up to set email alerts
|

The ICT-based fluorescence and colorimetric dual sensing of endogenous hypochlorite in living cells, bacteria, and zebrafish

Abstract: This work demonstrates a novel chemosensor, SPTPA, that exhibits fluorescence and colorimetric dual sensing of hypochlorite with an ICT ON strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Living cell imaging cannot provide satisfying details about the biological effects of biological imaging reagents, , while in vivo imaging can provide a more informative view. In recent years, zebrafish has received great attention for live vertebrate imaging due to several noticeable advantages, such as simplicity of operator, high homology, and external fertilization. , Most importantly, in comparison with a mouse, zebrafish is optically transparent during early development so that optical imaging techniques can be readily used. Thus, we use zebrafish to test the potential for in vivo bioimaging of the PDBCz@PVP NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Living cell imaging cannot provide satisfying details about the biological effects of biological imaging reagents, , while in vivo imaging can provide a more informative view. In recent years, zebrafish has received great attention for live vertebrate imaging due to several noticeable advantages, such as simplicity of operator, high homology, and external fertilization. , Most importantly, in comparison with a mouse, zebrafish is optically transparent during early development so that optical imaging techniques can be readily used. Thus, we use zebrafish to test the potential for in vivo bioimaging of the PDBCz@PVP NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish experiments proved that BK was organism-permeable and can monitor ClO − in living organisms. Importantly, BK is the first fluorescent turn-off sensor capable of sensing ClO − in zebrafish ( Table S1 ) [ 1 , 38 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interest in quantification of reactive oxygen species (ROS) has grown owing to the indispensable role played by ROS in pathological and physiological processes [ 1 , 2 , 3 , 4 , 5 ]. For instance, recent research revealed that cancer cells steadily produce high concentrations of intracellular ROS, owing to carcinogenic deformation [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…7a and b) based on spiropyran and triphenylamine, which can recognise ClO − with high selectivity. 54 Free probe 28 exhibited two sharp absorption peaks at 298 nm and 408 nm, but no emission signal was found with excitation at 408 nm. But after the addition of ClO − , three absorptions at 298, 371, and 530 nm were noted, and a clear fluorescence enhancement at 605 nm was also observed.…”
Section: Fluorescent Probes Based On a Triphenylamine Platform For An...mentioning
confidence: 96%